Mineralogical Characteristics of Phosphate Tailings for Comprehensive Utilization - Song Mao; Qin Zhang (Advances in Civil Engineering)
The mineralogical characteristics of a phosphate tailing were studied, and the occurrence state, mineral types, and embedded characteristics of phosphorus in the phosphate tailings were ascertained. The results show that the main minerals in the phosphate tailings are collophane. The main gangue minerals are quartz, dolomite, calcite, a small amount of potassium feldspar, plagioclase, chlorite, etc. Monazite was found in phosphate tailings. In addition, the coarse grain size of quartz and feldspar and fine embedded particle size of calcite and dolomite are also the main factors affecting the mineral processing of phosphate tailings. According to the analysis of mineralogical characteristics, the physical and chemical properties of phosphate tailings provided the basis for comprehensive utilization of phosphorus resources.